Effect of Refractive Index on Photon Natural Mass and Wavelength (Baghdad Science Journal, 2019)
In this article it is proved experimentally that the photon is a particle that has mass and constant wavelength by explaining the effect of refractive index on the wavelength and the natural mass of photon. It is very difficult to measure the mass of photon, a simple and easy process was proposed in this paper to calculate the mass length of photon in vacuum (Y) and in medium (Y*), by measuring the length of laser beam in air (Lair) and in medium (Lmed). A new method was postulated to calculate refractive index by using these relations (n = Y*/Y), and (n = Lmed / Lair) which supposed a new theory of light.